2008
DOI: 10.1016/j.clinbiochem.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Vascular versus myocardial dysfunction in acute coronary syndrome: Are the adhesion molecules as powerful as NT-proBNP for long-term risk stratification?

Abstract: Objectives-To determine if elevations of adhesion molecules in acute coronary syndrome (ACS) are useful for risk stratification.Design and methods-A cell adhesion array (Randox Ltd.) and NT-proBNP were measured in 216 ACS patients.Results-Kaplan-Meier and Cox models indicate early elevations of NT-proBNP but not the adhesion molecules are predictive of future death/myocardial infarction.Discussion-Elevations of adhesion molecules early after pain onset in ACS are not useful for long-term risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The use of sensitive troponin assays has helped with better diagnosis [8], but additional biomarkers would be especially useful to identify patients at long-term risk after presentation. A few acute-care markers such as cardiac troponin (cTn), natriuretic peptides and C-reactive protein (CRP), have been shown to have longerterm predictive value in patients with ACS [7,[9][10][11][12][13][14][15][16] but there are additional patients at risk who are not identified, perhaps in part because none of these biomarkers provides information about atherosclerotic plaque instability. A sensitive and specific early biomarker of atherosclerotic plaque instability would assist in risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The use of sensitive troponin assays has helped with better diagnosis [8], but additional biomarkers would be especially useful to identify patients at long-term risk after presentation. A few acute-care markers such as cardiac troponin (cTn), natriuretic peptides and C-reactive protein (CRP), have been shown to have longerterm predictive value in patients with ACS [7,[9][10][11][12][13][14][15][16] but there are additional patients at risk who are not identified, perhaps in part because none of these biomarkers provides information about atherosclerotic plaque instability. A sensitive and specific early biomarker of atherosclerotic plaque instability would assist in risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have demonstrated significantly raised soluble Pselectin levels in patients with AMI (77-84), unstable angina (85)(86)(87)(88) and cohorts of patients with any ACS (89,90). However conflicting results have also been reported, with two reports that P-selectin does not help to predict adverse events in patients with ACS and two studies that did not detect any elevation of plasma P-selectin levels in patients with ACS compared with controls (91)(92)(93).…”
Section: P-selectinmentioning
confidence: 99%